Constraints for collective action in Bulgarias irrigation sector - Insa Theesfeld (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2001)
Water for irrigation and irrigation infrastructure are both common pool resources, due to their low excludability and high rivalry. The well-known common pool resource dilemma is often the consequence. Collective action may be a way how societies can overcome this dilemma. First results from a three-month empirical field study in Bulgaria are presented trying to explain how actor groups characteristics, such as lack of trust between community members and effective institutional settings at the local level, such as information asymmetry, limited sanctioning and enforcement mechanisms and almost no monitoring mechanisms provide conditions under which opportunistic behaviour dominates. The effective rules-in-use in local communities are presented. The simplest example is watering crops without paying the water price. Individuals will use their power to maintain their opportunistic strategies and, consequently, they will not agree to any rule change. Moreover, the actors' attitude towards collective action is very pessimistic. This has a crucial impact on the evolving of credible commitment which is one prerequisite for collective action. The effects on water management can be severe and the common pool resource dilemma situation may continue. This article questions if there are additional influencing variables inherited from the transformation process that will have an impact on the institutional change and constrain the emergence of collective action solutions. The discussion is based on empirical material from Varbiza village in the south of Bulgaria.
Keywords: 330; Bewässerung; Allmenderessource; Bulgarien